EFEKTIVITAS PEMBELAJARAN BERBASIS MASALAH (PROBLEMBASED LEARNING) DALAM MENINGKATKAN PEMAHAMAN KONSEP BIOLOGI: SEBUAH SYSTEMATIC REVIEW DAN META-ANALISIS - Misno, Fina; Yatin Mulyono (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2025)
Understanding biological concepts is a crucial component in science education but remains a challenge at the junior and senior high school levels. One contributing factor is the dominance of conventional teaching methods that limit active student engagement. This study aims to evaluate the effectiveness of the Problem-Based Learning (PBL) model in improving students’ conceptual understanding in biology. The research employed a systematic review and meta-analysis approach, involving eight national quantitative studies that met the inclusion criteria, such as experimental design, complete statistical data, and secondary school student participants. The data analyzed included means, standard deviations, sample sizes, and calculated effect sizes using Cohen’s d formula. The findings reveal that the implementation of PBL consistently results in a significant positive effect, with an average effect size of 2.14, categorized as large. This indicates that PBL not only enhances conceptual understanding but also fosters active involvement, critical thinking, and collaboration among students in biology learning. Therefore, PBL is recommended as an innovative and effective instructional strategy that should be widely implemented in secondary biology education.